2015
DOI: 10.1007/s13593-015-0330-1
|View full text |Cite
|
Sign up to set email alerts
|

Agroforestry promotes soybean yield stability and N2-fixation under water stress

Abstract: Agroforestry systems can buffer crop performance against the impacts of climate change, particularly decreases in the availability of soil water. Nonetheless, farmers are reluctant to adopt agroforestry systems due to concerns of yield losses, predominantly in the tree-crop competitive zone. Yet little is known about crop performance in the tree-crop competitive zone under water limited conditions. We therefore studied the effect of a full season water deficit on soybean N 2 -fixation, nodulation, and yield in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
37
1
1

Year Published

2016
2016
2021
2021

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 48 publications
(42 citation statements)
references
References 35 publications
3
37
1
1
Order By: Relevance
“…Based on previous work at the same experimental site, the percentage of N derived from atmosphere (%Ndfa), measured from soybean leaves, was significantly higher in the agroforest as compared to the monoculture (Nasielski et al., ). Specifically, at the “V5” (vegetative) stage of annual soybean growth, %Ndfa was reported as 2.7 ± 0.9 and 64.3 ± 4.1 for the monoculture and agroforest, respectively.…”
Section: Methodsmentioning
confidence: 95%
“…Based on previous work at the same experimental site, the percentage of N derived from atmosphere (%Ndfa), measured from soybean leaves, was significantly higher in the agroforest as compared to the monoculture (Nasielski et al., ). Specifically, at the “V5” (vegetative) stage of annual soybean growth, %Ndfa was reported as 2.7 ± 0.9 and 64.3 ± 4.1 for the monoculture and agroforest, respectively.…”
Section: Methodsmentioning
confidence: 95%
“…Recently, Nasielski et al. (2015) found that soybean (in the tree‐crop competitive zone of a 27‐year‐old tree‐based intercropping agroforestry system) allocated a larger proportion of nodule biomass to the lower root system under water limitation. These intercropped soybeans relied on N 2 ‐fixation to a higher extent to meet their N demand compared to soybeans grown in monocropping.…”
Section: Discussionmentioning
confidence: 99%
“…In contrast, temperate AC can stabilize crop performance by moderating drought (Nasielski et al. ), reducing erosion and improving soil fertility (Udawatta et al. , Torralba et al.…”
Section: Discussionmentioning
confidence: 99%